Analisis Sentimen Berbasis Emoticon pada Komentar Instagram Bahasa Indonesia Menggunakan Naïve Bayes - Kristian Adi Nugraha (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The usage of social media growing rapidly, especially after the smartphone was invented. Because the number of social media users was quite a lot, companies prefer to promote their products through social media like Instagram. But, unlike TV or radio, social media is a two-way communication media, that makes users can respond directly to the content created by the company. Comments given by users have various types of sentiment, like positive or negative comments. In addition to using text, comments also often contain emoticons to support the message. This study tries to analyzing sentiment based on the usage of emoticons inside them using the Naïve Bayes algorithm. Based on the test results, the accuracy result is quite good, it is about 96.3% correct in sentiment classification.